Endobronchial ultrasound-guided transbronchial needle aspiration of pulmonary artery tumors: A systematic review (with video) - Harris, Kassem (Endosc Ultrasound, 2015)
Convex probe endobronchial ultrasound (CP-EBUS) was originally introduced as a diagnostic and staging tool for lung cancer and subsequently utilized for diagnosis of other malignant and benign mediastinal diseases such as melanoma, lymphoma, and sarcoidosis. More recently, CP-EBUS has been successfully used for the visualization and diagnosis of pulmonary emboli and other vascular lesions including primary and metastatic pulmonary artery (PA) tumors. In this review, we will underline the role of EBUS-guided transbronchial needle aspiration (EBUS-TBNA) for the diagnosis of pulmonary arterial tumors such as sarcomas and tumor emboli. We will concisely discuss the clinical applications of EBUS-TBNA and the types of pulmonary arterial tumors and their different diagnostic modalities. We searched the Cochrane Library and PubMed from 2004 to 2014 to provide the most comprehensive review. Only 10 cases of EBUS-TBNA for intravascular lesions were identified in the literature. Although many cases of EBUS and EUS-guided transvascular tumor biopsies were described in the literature, there were no reported cases of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for intravascular tumor biopsies. Except for one paper, all cases were published as case reports.